Conjoint analysis of OPRPN and SMR3A protein expression as potential predictive biomarkers for head and neck squamous cell carcinoma after radiotherapy - Rong, Chao; Grünow, Jennifer; Thierauf, Julia; Lucena Porcel, Carlota; Major, Gerald; Holzinger, Dana; Dyckhoff, Gerhard; Kern, Johann; Lammert, Anne; Scherl, Claudia; Rotter, Nicole; Plinkert, Peter K.; et al. (Oncology reports, 2022)
Increased submaxillary gland androgen‑regulated protein 3A (SMR3A) expression was previously shown to serve as an independent risk factor for oropharyngeal squamous cell carcinoma (OPSCC) and as a surrogate biomarker for active estrogen receptor 2 signaling in radioresistant tumor cells. In the present study, it was aimed to unravel the expression and clinical significance of another member of the opiorphin family, opiorphin prepropeptide (OPRPN), in the radiotherapy for head and neck squamous cell carcinoma (HNSCC). Expression of SMR3A and OPRPN were analyzed for the prior and post fractionated irradiation (4x2 Gy) by double immunofluorescence staining in established HNSCC cell lines as well as by immunohistochemical (IHC) staining in ex vivo tumor tissues. Next, in a retrospective experimental cohort study, primary tumor samples from OPSCC patients (n=96), who received definitive surgery and adjuvant radiotherapy were reviewed, and expression levels of OPRPN protein were detected by IHC. Immunoreactivity scores (IRS) were associated with pathological and clinical risk factors by Chi‑square analysis. Survival analysis was performed by using the Kaplan‑Meier plot, log‑rank test and Cox regression analysis. The expression levels of OPRPN and SMR3A protein were both induced by fractionated irradiation in vitro and ex vivo. In primary tumor samples, IRS of OPRPN was significantly higher than scores of SMR3A expression and positively correlated with expression patterns of SMR3A. SMR3A was confirmed to serve as an unfavorable factor, while OPRPN protein had no significant association with the clinical outcome of patients with OPSCC. A combinational analysis revealed that the subgroup with SMR3AhighOPRPNlow staining pattern had the worst clinical outcome among the various subgroups. Multivariate Cox regression analyses indicated that high expression of SMR3A serves as an independent unfavorable biomarker, while increased expression of OPRPN appears to exert protective function. In summary, the present study indicated that SMR3A and OPRPN serve as potential prognostic markers for HNSCC after radiotherapy.
Gesehen am 31.01.2023